Analisis Kuantitatif Terhadap Faktor Penentu Integritas Akademik Dosen Di Pendidikan Tinggi Indonesia - Yudatama , Uky; Sugiarti, Rini; Erlangga, Erwin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
Research on lecturers' academic integrity is still relatively limited, especially those that simultaneously examine organizational and individual factors in a single structural model. This study aims to analyze the factors influencing lecturers' academic integrity in Indonesia by placing organizational commitment as a mediating variable. The study used a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method on 63 lecturers in Indonesia. The results showed that ethical leadership significantly influenced organizational commitment (β = 0.311; p < 0.01). Workload negatively influenced lecturers' academic integrity (β = −0.183; p < 0.05). Meanwhile, ethical competence (β = 0.263; p < 0.05), incentives (β = 0.215; p < 0.05), and academic sanctions (β = 0.222; p < 0.05) had a significant positive effect on academic integrity. In contrast, organizational culture did not show a significant effect on academic integrity (β = −0.147; p > 0.05). In addition, organizational commitment had a strong influence on lecturers' academic integrity (β = 0.391; p < 0.01) and was proven to mediate the relationship between ethical leadership and academic integrity (indirect β = 0.122; p < 0.05). The R² value of 0.709 indicates that 70.9% of the variation in academic integrity can be explained by the research model. This research contributes to the development of academic integrity studies by integrating leadership, organizational, and individual factors in one PLS-SEM-based empirical model. Keywords: Academic Integrity; Ethical Leadership; Organizational Culture; Workload; Ethical Competence; Organizational Commitment